Metagenomics-based analysis of mobile genetic elements and antibiotic/metal resistance genes carried by treated wastewater - Chahnez Naccache; Chourouk Ibrahim; Abdennaceur Hassen; Maha Mezghani Khemakhem (PeerJ, 2025)
Wastewater treatment plants in Tunisia are recognized as key locations for the spread of antibiotic and heavy metal resistance genes among bacteria. Despite the widespread presence of pollutants in these treatment systems, there is still a significant gap in our understanding of resistance dynamics. This study focused on analyzing the bacterial community and resistome-mobilome profiles of the Charguia wastewater treatment plant (WWTP). Using metagenomics sequencing, six samples from the influent, sludge, and effluent were thoroughly examined. Our research findings indicated the prevalence of Proteobacteria and high levels of Bacteroidota, Firmicutes, Campylobacterota, and Patescibacteria. After conducting a species level analysis, we identified important species such as Pseudomonas psychrophila, Pseudomonas fragi, Pseudomonas lundensis, Acinetobacter johnsonii, and Thiothrix unzii linked to antibiotic resistant genes (ARGs) like mdtA and merR1 and heavy metal resistance genes (MRGs), including czcA and cnrA. Our study illustrated the persistence of specific species in the effluent due to the co-occurrence of ARGs/MRGs and mobile genetic elements (MGE). Notably, IncQ and IncP were found to be associated with mdtA, mexR, arsR1, and merR. The conclusions drawn from our research suggest that the WWTP has been potentially effective in reducing multidrug resistance.